Reconstruction and Analysis of a Genome-Scale Metabolic Model of Ganoderma lucidum for Improved Extracellular Polysaccharide Production - Ma, Zhongbao; Ye, Chao; Deng, Weiwei; Xu, Mengmeng; Wang, Qiong; Liu, Gaoqiang; Wang, Feng; Liu, Liming; Xu, Zhenghong; Shi, Guiyang; Ding, Zhongyang (Frontiers in Microbiology, 2018)
In this study, we reconstructed for the first time a genome-scale metabolic model (GSMM) of Ganoderma lucidum strain CGMCC5.26, termed model iZBM1060, containing 1060 genes, 1202 metabolites, and 1404 reactions. Important findings based on model iZBM1060 and its predictions are as follows: (i) The extracellular polysaccharide (EPS) biosynthetic pathway was elucidated completely. (ii) A new fermentation strategy is proposed: addition of phenylalanine increased EPS production by 32.80% in simulations and by 38.00% in experiments. (iii) Eight genes for key enzymes were proposed for EPS overproduction. Model iZBM1060 provides a useful platform for regulating EPS production in terms of system metabolic engineering for G. lucidum, as well as a guide for future metabolic pathway construction of other high value-added edible/ medicinal mushroom species.